The Impact of Assets Revaluation on Banking Capital Adequacy Ratio - Rahmayanti, A Y; Anesti, B D (KnE Social Sciences, 2018)
The financial industry, especially the banking industry, requires the bank to maintain its capital structure well. Bank can change the accounting policy of fixed assets into revaluation method. This study would like to see the impact of assets revaluation and its effect on the capital structure. There are two elements of capital structure that can affect the CAR ratio, that is, core capital and complementary capital. In the supplementary capital, there is an asset revaluation reserve This study looks at a bank that revalued its fixed assets since 2014. Based on the results of the study, it was concluded that the revaluation of assets could improve the capital structure of these banks, especially it increases the capital adequacy ratio. Keywords: assets revaluation, capital adequacy ratio, risk weighted assets